A Comparative Study of Thai and Italian Historic Stone Statues: A Case Study of Khao Mo at Wat Prayurawongsawat and the Apennine Colossus - Selanon, Pattamon (Journal of Arts and Thai Studies, 2025)
Background and Objectives: This study analyzes and compares the cultural significance of historic stone sculptures from Thailand and Italy: Khao Mo at Wat Prayurawongsawat in Bangkok and the Colossus of the Apennines in Italy. These monumental works are not merely landscape ornaments but serve as artistic, religious, and cultural symbols that embody profound narratives of cosmology, mythology, and power. The main objective is to understand how such sculptures reflect cultural values, beliefs, and the idea of integrating art with nature. The study also proposes approaches for conserving and presenting heritage that bridges local and global contexts. By comparing works with different origins but similar thematic intentions, this research highlights the role of heritage in transmitting identity, memory, and belief systems. Methods: The research adopts a qualitative comparative analysis, examining the context, spatial setting, and forms of both monuments via the field surveys, photographic documentation, and analyses of construction techniques, materials, and symbolic elements. These data were synthesized to interpret the interrelations among sculptures, landscapes, and spiritual dimensions. Results: Khao Mo at Wat Prayurawongsawat reflects Thai Buddhist cosmology, recreating a sacred landscape symbolizing Mount Meru. It integrates natural elements such as water, vegetation, and religious iconography to create an atmosphere conducive to meditation and spiritual reflection. In contrast, the Colossus of the Apennines embodies Renaissance and Mannerist ideals in Italy, employing mythological symbolism, artistic ambition, and architectural integration with nature. Beyond its artistic presence, the sculpture contains functional features, including interior chambers and a working water system, reflecting the era’s attempt to integrate art with functionality. Application of this study: The findings indicate that heritage conservation must give priority to the context and the cultural values embedded within the structure to enhance restoration, interpretation, and communication of heritage significance. Comparative analysis further provides a foundation for cross-cultural knowledge exchange in art and architectural conservation, particularly within the framework of global heritage management, which requires interdisciplinary collaboration to preserve the profound meaning reflected in the works. Conclusions: The comparison of Khao Mo and the Colossus of the Apennines demonstrates that historic monumental sculptures in public spaces can reflect cultural identity, religious worldviews, and artistic intent in profound ways. Despite differences in origin and style, both exemplify harmonious integration of art and nature, expressing shared human concerns with spirituality, myth, and memory. This study contributes to broader heritage discourse by emphasizing that conservation should extend beyond physical form to encompass intangible meanings. Cross-cultural perspectives on monumental stone sculptures enrich understanding of how societies interpret the relationship between humans, nature, and the sacred. They also highlight the necessity of contextual interpretation and interdisciplinary approaches that link art history, architecture, landscape architecture, and cultural studies. Ultimately, this research establishes a foundation for future comparative heritage conservation studies and promotes global awareness of the diverse ways in which meaning is conveyed through monumental art.